Elephantine, Ägypten. Gesamtprojekt Elephantine und Teilprojekt Lebenswirklichkeiten (Realities of Life). Das 50. Grabungsjubiläum und aktuelle Arbeiten - Sigl, Johanna (e-Forschungsberichte des DAI, 2019)
January 9th, 1969 was the first day of excavation of the DAI Cairo and its partners on Elephantine. In the year of the 50th anniversary of the project, its success was celebrated amongst other with a conference focusing on settlement archaeology. Half a century of field research has produced a wealth of data which have fundamentally advanced our conception of Ancient Egyptian culture – and the development of research questions and research methodologies inspires ongoing research in ever new directions. In 2018/2019 season the DAI’s works focused especially on the execution of archaeometric methods on newly excavated finds and the conservation of one of the last preserved buildings of the colonial period in Aswan area.